The evaluation of some hematological parameters of human tuberculosis in Thi-Qar Province - Al-Tamemi , Manal (University of Thi-Qar Journal of Science)
The present study aimed to evaluation of erythrocyte sedimentation rate (ESR), hemoglobin (Hb.) levels, white blood cell count (WBCs) in active and latent tuberculosis patients in Thi-Qar province,Iraq. This study included 210 samples (70 patients, 70 household contacts and 70 control ) with age’s ≤10 to ≥70 years who were referred to ALNasiriya Center of Tuberculosis and Chest Diseases from the period September 2012—July 2013.The study showed that the values erythrocyte sedimentation rate indicated a significant increase (P≤0.05) in patients and HHCs groups when compared with the value of control group (42.64, 22.93 vs. 8.79 mm/h, respectively). While the results showed a significant decrease (P≤0.05) in the hemoglobin, (Hb.) levels of patients group and HHCs when compared with control group (8.63 and 11.84 vs.13.17 gm/dl, respectively). The means of white blood cell (WBCs), showed a significant increase in patient and household when compared with correspondent value of control groups.